Medial plantar artery flap: a versatile workhorse flap for foot reconstruction, our experience - Shah, Sankit B.; Shah, Ankit; Tomar, Janvi; Patel, Dhruv V.; Ribadia, Purandar (International Journal of Research in Medical Sciences, 2023)
Soft tissue defect in the foot is commonly seen as it is more prone to trophic ulcers since it is the main weight bearing area of the body. Reconstruction of the weight bearing area of the foot requires the provision of a stable, supple, durable and preferably sensate skin coverage. Following Sir Gilli’s principle of replacing like with like, medial plantar artery flap provides an anatomically similar, glabrous skin for coverage on the plantar surface. In the present study, we share our clinical experience with the use of medial plantar artery flap for coverage of soft tissue defect over sole of foot. At our institution, a total of 10 patients presented with soft tissue defect of the sole, underwent medial plantar artery flap coverage. All the 10 patients were diagnosed cases of type 2 DM. patient outcome was assessed according to patients’ age distribution, duration of surgery, hospital stay, and post operative complications. Out of all the 10 patients, 5 were male and 5 were female. All the flaps healed uneventfully without major complications like partial flap necrosis. Donor site was covered with split thickness skin graft. There was suture site dehience in 2 cases which healed with secondary healing. Medial plantar artery flap has been described as an optimal reconstructive option for this type of soft tissue defect.